Situational-event model of the hybrid patterns recognition for heterogeneous data processing in complex systems - Zakhozhay, O.I. (Математичне моделювання в економіці, 2019)
In the article represented the new situational-event model of hybrid patterns recognition. This model based on representation a heterogeneous data of a complex system in the form of patterns set, sets of external conditions characteristics as manifestations of a current situation, a static component of a situation - in the form of stationary informativity characteristics, a dynamic component in the form of a nonstationary informativity characteristics and the set of classes as recognitions result. The developed model using provides a priory level of classification reliability, based on analysis of a smaller set but the most informative signs.